Test–retest reliability of new and conventional echocardiographic parameters of left ventricular systolic function - Baron, Tomasz; Berglund, Lars; Hedin, Eva-Maria; Flachskampf, Frank A. (Clinical research in cardiology, 2019)
Background Reliability of left ventricular function measurements depends on actual biological conditions, repeated registrations and their analyses. Objective To investigate test–retest reliability of speckle-tracking-derived strain measurements and its determinants compared to the conventional parameters, such as ejection fraction (EF), LV volumes and mitral annular plane systolic excursion (MAPSE). Methods In 30 patients with a wide range of left ventricular function (mean EF 46.4 ± 16.4%, range 14–73%), standard echo views were acquired independently in a blinded fashion by two different echocardiographers in immediate sequence and analyzed off-line by two independent readers, creating 4 data sets per patient. Test–retest reliability of studied parameters was calculated using the smallest detectable change (SDC) and a total, inter-acquisition and inter-reader intra-class correlation coefficient (ICC). Results The smallest detectable change normalized to the mean absolute value of the measured parameter (SDCrel) was lowest for MAPSE (10.7%). SDCrel for EF was similar to GLS (14.2 and 14.7%, respectively), while SDCrel for CS was much higher (35.6%). The intra-class correlation coefficient was excellent (> 0.9) for all measures of the left ventricular function. Intra-patient inter-acquisition reliability (ICCacq) was significantly better than inter-reader reliability (ICCread) (0.984 vs. 0.950, p = 0.03) only for EF, while no significant difference was observed for any other LV function parameter. Mean intra-subject standard deviations were significantly correlated to the mean values for CS and LV volumes, but not for the other studied parameters. Conclusions In a test–retest setting, both with normal and impaired left ventricular function, the smallest relative detectable change of EF, GLS and MAPSE was similar (11–15%), but was much higher for CS (35%). Surprisingly, reliability of GLS was not superior to that of EF. Acquisition and reader to a similar extent influenced the reliability of measurements of all left ventricular function measures except for ejection fraction, where the reliability was more dependent on the reader than on the acquisition.